Identification of an immune-related six-long noncoding RNA signature as a novel prognosis biomarker for adenocarcinoma of lung. Issue 1 (29th January 2021) - Miao, Huikai; Chen, Dongni; Li, Rongzhen; Hu, Jia; Chen, Youfang; Xu, Chunmei; Wen, Zhesheng
Abstract: Background: Lung adenocarcinoma (LUAD) is a heterogeneous disease with high mortality. Close attention has been paid to immunotherapy in LUAD treatment. However, immunotherapy has produced different therapeutic effects because of immune heterogeneity. Long noncoding RNAs (lncRNAs) are survival prognostic indicators with functions in the immune process. The present study was designed to examine the predictive power of immune-related lncRNAs in LUAD prognosis and investigated potential molecular mechanisms. Methods: Transcriptome profiling and LUAD sample clinical information were retrieved from online database. The immune-related lncRNAs signature was identified by Cox regression. Survival analysis was used to verify the validity of the prognosis model. Then, possible biological functions were predicted and the abundance of infiltrating immune cells in LUAD samples were further analyzed. Results: An immune-associated lncRNAs signature was established by combining six lncRNAs. Patients with LUAD were stratified into high- and low-risk groups using the six lncRNAs signature. Patients in different risk levels had significantly different prognoses ( P <0.001), and the immune-associated lncRNAs signature was identified as an independent prognostic factor for LUAD. The functions of the lncRNA signature were confirmed as ubiquitin mediated proteolysis and signal sequence binding. The lncRNA signature negatively correlates with B-cell immune infiltration. Conclusion: A reliable immune-related lncRNAs prognosis model for LUAD was identified. lncRNAs played a vital role in the tumor immune process and were associated with the LUAD prognosis. Research of lncRNAs in B-cell immune infiltration could provide new insight into the immunotherapy of LUAD.